PROFESSIONAL IDENTITY STRUCTURE OF PHYSICAL THERAPISTS - Корчинський, Володимир; Пономаренко, Микола (SWorldJournal, 2024)
The main provisions of the formation of the professional identity of future specialists in physical therapy in institutions of higher education are considered. The structure of the professional identity of future specialists in physical therapy has been s